Case report: Adult with bipolar disorder and autism treated with ketamine assisted psychotherapy - Harris, Christopher P.; Jones, Becky; Walker, Kathryn; Berry, Meredith S. (Frontiers in Psychiatry, 2024)
Background: Evidence has increased in recent years regarding the potential for ketamine to serve as a novel treatment option for a range of conditions, particularly depression (unipolar and bipolar). However, research regarding ketamine as a potential therapeutic for Autism Spectrum Disorder (ASD) is lacking, despite high overlap with bipolar depression and theoretical foundations for its use. Case Presentation: A 29-year-old man with bipolar disorder and autism spectrum disorder, type 2 diabetes, presented with mood swings and suicidal thoughts, and anger outbursts occurring daily. The patient was referred by a psychiatrist due to irritability and outbursts during the previous 5 months. These outbursts were unable to be controlled by the medications prescribed, and included yelling and screaming, and the patient was unable to speak with the psychiatrist. The patient underwent ketamine assisted psychotherapy with 6 initial IV infusions of ketamine over a 1 month period followed by 2 booster IV ketamine infusions.Following ketamine treatment, dramatic reductions in outbursts were observed as well as reductions in anxiety, suicidality, and depression scores. Conclusions: This case study adds to the scant literature regarding ketamine treatment for individuals with bipolar disorder and ASD.We did not find ASD to be a contraindication for IV ketamine and ketamine assisted psychotherapy. Reductions in anger outbursts, anxiety, suicidality, and depression suggest ketamine treatment might be tailored to individuals with bipolar disorder and ASD, and additional systematized research is warranted. Although potential mechanisms of action are not clear, these data add to the discussion regarding clinical practice considerations and the potential for ketamine to improve quality of life and associated metrics.